Firm exit during economic slowdowns: does foreign ownership matter? - Rocha, V. C. (2012)
Do multinationals’ activities contribute to the severity of global economic crisis by quickly closing down facilities or otherwise allow to mitigating some of the worst effects, by remaining rooted in the local economy and thus reducing lay-offs and output contraction in the host countries? The present paper provides an empirical analysis on the link between foreign ownership and firm survival over an almost 20-year period and during two economic downturns in particular, using an extensive firm-level database and applying hazard models. We analyse the determinants of exit of firms and investigate whether there are significant differences in the hazard rates of foreign and domestic firms when controlling for firm and industry specificities. Additionally we assess whether the foreignness effect alters during economic downturns and whether any spillovers arise from the multinationals’ presence in the industry. After controlling for several firm and industry specific characteristics, we find that foreign firms exhibit higher failure rates over the time period as a whole. However, during economic slowdowns domestic and foreign firms do not exhibit different chances of survival and exit. Finally, regarding potential spillovers, our results suggest that foreign presence may impact positively upon local firms’ survival.